Authoritarian elections, state capacity, and performance legitimacy: Phases of regime consolidation and decline in Suharto's Indonesia. Issue 1 (January 2018) - Mietzner, Marcus
Political scientists have recently debated the extent to which strong state capacity helps authoritarian regimes to win elections and extend their rule. This article proposes that it is not only important to disaggregate the various forms of state capacity mobilized for that purpose, but also to analyze the sequence with which autocracies deploy them. Using Suharto's New Order regime in Indonesia as a case study, I argue that regimes mobilize different forms of state capacity in distinct phases of their development, and that the sequencing of this deployment can have implications for the regime's endurance. Suharto, for example, gradually reduced the importance of coercion as he increasingly focused on the state's ability to facilitate elite co-optation and economic patronage. This helped to extend the regime's endurance as long as the economy flourished, but also made it vulnerable to the fluctuations in the world economy that caused its demise in 1998.